The effect of SGLT-2i administration on red blood cell distribution width in patients with heart failure and type 2 diabetes mellitus: A randomized study - Katsiadas, Nikolaos; Xanthopoulos, Andrew; Giamouzis, Grigorios; Skoularigkis, Spyridon; Skopeliti, Niki; Moustaferi, Evgenia; Ioannidis, Ioannis; Patsilinakos, Sotirios; Triposkiadis, Filippos; Skoularigis, John (Frontiers in Cardiovascular Medicine, 2022)
Background: Recent studies suggest that the pivotal mechanism of sodium glucose co-transporter-2 inhibitors (SGLT-2i) favorable action in patients with heart failure (HF) and type 2 diabetes mellitus (DM) is the stimulation of erythropoiesis via an early increase in erythropoietin (EPO) production which leads to hematocrit rise. Red blood cell distribution width (RDW) is a simple hematological parameter which reflects the heterogeneity of the red blood cell size (anisocytosis). Since, EPO has been also implicated in the pathophysiology of RDW increase, the current mechanistic study examined the effect of SGLT-2i administration on red blood cells size (RDW) in patients with HF and DM. Methods: The present was a prospective single-center study. Patients (N=110) were randomly assigned to dapagliflozin (10 mg a day on top of antidiabetic treatment) or the control group. Inclusion criteria were: a) age > 18 years, b) history of type 2 DM and hospitalization for HF exacerbation within 6 months. The evaluation of patients (at baseline, 6 and 12 months) included clinical assessment, laboratory blood tests, and echocardiography. Data were modelled using mixed linear models with dependent variable the RDW index. In order to find factors independently associated with prognosis (1-year death or HF rehospitalization), multiple logistic regression was conducted with death or HF rehospitalization as dependent variable. Results: An RDW increase both after six and after twelve months was observed in the SGLT-2i (dapagliflozin) group (p<0.001 for all time comparisons), whereas RDW didn’t change significantly in the control group. The increase in RDW was positively correlated with EPO, while negatively correlated with ferritin and folic acid (p<0.005 for all). RDW was significantly associated with 1-year death or rehospitalization, after adjusting for group (SGLT-2i vs control), age, gender, smoking and BMI at baseline. Conclusions: RDW increased with time in patients with HF and DM who received SGLT-2i (dapagliflozin). The increased RDW rates in these patients may stem from the induction of hemopoiesis from dapagliflozin. RDW was found to be independently associated with outcome in patients with HF and DM, irrespective of the administration of dapagliflozin or not.